Eicosanoid Profile of Influenza A Virus Infected Pigs - Daniel Schultz; Karen Methling; KoInfekt Study Group; Michael Rothe; Michael Lalk (Metabolites, 2019)
Respiratory tract infections caused by the Influenza A virus (IAV) are a worldwide problem for human and animal health. Within this study, we analyzed the impact of IAV infection on the immune-related lipidome (eicosanoids) of the pig as new infection model. For this purpose, we performed HPLC-MS/MS using dynamic multiple reaction monitoring and analyzed lung, spleen, blood plasma and bronchoalveolar lavages. IAV infection leads to collective changes in the levels of the analyzed hydroxyeicosatrienoic acids (HETEs), hydroxydocosahexaenoic acids (HDHAs) and epoxyeicosatrienoic acids (EETs), and moreover, unique eicosanoid changes in several sample types, even under mild infection conditions. In accordance with different mouse infection studies, we observed infection-related patterns for 12-HETE, 15-HETE and 17-HDHA, which seem to be common for IAV infection. Using a long-term approach of 21 days we established an experimental setup that can be used also for bacterial-viral coinfection experiments.